2018
DOI: 10.1002/2017jc013426
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Heat Budget Dynamics During Two La Niña Marine Heat Wave Events Along Northwestern Australia

Abstract: Two marine heat wave events along Western Australia (WA) during the alternate austral summer periods of 2010/2011 and 2012/2013, both linked to La Niña conditions, severely impacted marine ecosystems over more than 12° of latitude, which included the unprecedented bleaching of many coral reefs. Although these two heat waves were forced by similar large‐scale climate drivers, the warming patterns differed substantially between events. The central coast of WA (south of 22°S) experienced greater warming in 2010/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…MHWs can also increase the likelihood of ecosystem changes through mechanisms other than thermal stress. Reported ecological and economic impacts of recent MHW events include local extinction of mangrove and kelp forests 2 , coral bleaching [3][4][5] , elevated mortalities of invertebrates 6 , fishes, seabirds 7 , and marine mammals, and invasions of non-native species 8 . These changes have altered global biodiversity and caused societal impacts 9 .…”
mentioning
confidence: 99%
“…MHWs can also increase the likelihood of ecosystem changes through mechanisms other than thermal stress. Reported ecological and economic impacts of recent MHW events include local extinction of mangrove and kelp forests 2 , coral bleaching [3][4][5] , elevated mortalities of invertebrates 6 , fishes, seabirds 7 , and marine mammals, and invasions of non-native species 8 . These changes have altered global biodiversity and caused societal impacts 9 .…”
mentioning
confidence: 99%
“…furthermore, the resilience of these ecosystems [Botsford et al, 2009;Kool et al, 2011]. In Western Australia, for example, strong recent coral reef bleaching events is in part due to the horizontal advective transport of heat [Xu et al, 2018].…”
Section: Motivationsmentioning
confidence: 99%
“…Recently, Kataoka et al (2017) calculated the mixed layer temperature balance associated with Ningaloo Niño events and found that shortwave radiation contributes to the coastal warming in both locally and non-locally amplified modes due to the warming produced by the climatological surface heat flux enhanced by the shallow mixed-layer depth (MLD) anomaly during the onset. Moreover, Xu et al (2018) compared the difference in SST warming patterns between the 2012/2013 event with the 2010/2011 event and found that the difference in the relative importance of surface heat fluxes and heat advection between the two events is mostly responsible for the different spatial distribution of the warming.…”
Section: Introductionmentioning
confidence: 99%